Palmitic Acid Induces MicroRNA-221 Expression to Decrease Glucose Uptake in HepG2 Cells via the PI3K/AKT/GLUT4 Pathway - Fang Huang; Jie Chen; Jingwen Wang; Pingping Zhu; Wenting Lin (2019)
Obesity-related insulin resistance and high fatty acid concentrations occur during the development of type 2 diabetes mellitus. The role of high concentrations of plasma-free fatty acids is not fully understood. In this study, palmitic acid (PA, 0.8 mM for 24 h) induced the expression of miR-221 that bound to phosphoinositide 3-kinases (PI3K) mRNA to inhibit glucose uptake by HepG2 cells. Compared with controls, PA significantly decreased glucose uptake, increased insulin receptor substrate-2 (IRS-2) and miR-221 expression, and decreased phosphoinositide 3-kinase (PI3K), protein kinase B (AKT), and glucose transporter type 4 (GLUT4) mRNA expression. Luciferase reporter assay revealed that miR-221 binding inhibited PI3K expression. Transfection of HepG2 cells with an miR-221 mimic induced miR-221 expression and inhibited the PI3K/AKT pathway. PA decreased glucose uptake in HepG2 cells by inducing the expression of miR-221, which bound to PI3K mRNA and suppressed PI3K/AKT signaling. miR-221 may be a novel target for preventing and treating obesity-induced insulin resistance.